Developmental Exposure to a Human-Relevant Polychlorinated Biphenyl Mixture Causes Behavioral Phenotypes That Vary by Sex and Genotype in Juvenile Mice Expressing Human Mutations That Modulate Neuronal Calcium - Sethi, Sunjay; Keil Stietz, Kimberly P.; Valenzuela, Anthony E.; Klocke, Carolyn R.; Silverman, Jill L.; Puschner, Birgit; Pessah, Isaac N.; Lein, Pamela J. (Frontiers in Neuroscience, 2021)
Polychlorinated biphenyls (PCBs) are putative environmental risks for neurodevelopmental disorders. Here, we tested two hypotheses: (1) developmental exposure to a human-relevant PCB mixture causes behavioral phenotypes relevant to neurodevelopmental disorders; and (2) expression of human mutations that dysregulate neuronal Ca2+ homeostasis influence sensitivity to behavioral effects of developmental PCB exposures. To test these hypotheses, we used mice that expressed a gain-of-function mutation (T4826I) in ryanodine receptor 1 (RYR1), the X-linked fragile X mental retardation 1 (FMR1) CGG repeat expansion or both mutations (double mutant; DM). Transgenic mice and wildtype (WT) mice were exposed to the MARBLES PCB mix at 0, 0.1, 1 and 6 mg/kg/day in the maternal diet throughout gestation and lactation. The MARBLES PCB mix simulates the relative proportions of the twelve most abundant PCB congeners found in the serum of pregnant women at increased risk for having a child with a neurodevelopmental disorder. We assessed ultrasonic vocalizations at postnatal day 7 (P7), spontaneous repetitive behaviors at P25-P30, and sociability at P27-P32. Developmental PCB exposure reduced ultrasonic vocalizations in WT litters in all dose groups, but had no effect on ultrasonic vocalizations in transgenic litters. Developmental PCB exposure significantly increased self-grooming and decreased sociability in WT males in the 0.1 mg/kg dose group, but had no effect on WT females in any dose group. Genotype alone influenced ultrasonic vocalizations, self-grooming and to a lesser extent sociability. Genotype alone also influenced effects of PCBs on sociability. PCB levels in the brain tissue of pups increased in a dose-dependent manner, but within any dose group did not differ between genotypes. In summary, developmental PCB exposure phenocopied social behavior phenotypes observed in mice expressing human mutations that modify intracellular Ca2+ dynamics, and expression of these mutations alleviated PCB effects on ultrasonic vocalizations and repetitive behavior, and modified the dose-response relationships and sex-dependent effects of PCB effects on social behavior. These findings suggest that: (1) developmental PCB exposure causes behavioral phenotypes that vary by sex and genotype; and (2) sex-specific responses to environmental factors may contribute to sex biases in the prevalence and/or severity of neurodevelopmental disorders.